Britse invloed op atletiek in die Wes-Kaap tot 1932 - Van der Merwe, F. J. G.(Floris J. G.),1951- (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (M.A.) -- Universiteit van Stellenbosch, 1987.